Investigation on the structure and electrochemical performance of LiNi0.8Co0.1Mn0.1O2 modified with Sn. (20th December 2021) - Li, Zekun; Yu, Xiaofang; Lv, Yanpeng; Qi, Liang; Ma, Yue; zhang, Hongzhou; Song, Dawei; Shi, Xixi; Zhang, Lianqi
Highlights: Influence of Li2 SnO3 -coating and Sn-doping on NCM materials are compared. Sn-modified samples have high interfacial stability and low polarization in cycle. High cycle stability can be obtained for Li2 SnO3 -coated and Sn-doped NCM samples. The mechanism of improved performance of Sn-modified samples are studied. Abstract: Ni-rich layered cathode materials are promising cathode materials for lithium-ion batteries with high energy density. To reveal the influence of Sn-coating and doping on the structure and electrochemical performances of Ni-rich layered cathode materials, LiNi0.8 Co0.1 Mn0.1 O2, LiNi0.8 Co0.1 Mn0.1 O2 @xLi2 SnO3 and LiNi0.8−x Co0.1 Mn0.1 Snx O2 (x = 0.02 and 0.04) are designed and synthesized. The effect of lithium-tin-oxide coating and Sn-doping on the structural and electrochemical behavior of Ni-rich cathode material are compared and investigated. Compared with the bare LiNi0.8 Co0.1 Mn0.1 O2 cathode material, both LiNi0.8 Co0.1 Mn0.1 O2 @xLi2 SnO3 and Sn-doped LiNi0.8−x Co0.1 Mn0.1 Snx O2 (x = 0.02 and 0.04) samples exhibit better electrochemical performances. The capacity retention for Li2 SnO3 -coated and Sn-doped materials after 270 cycles at 0.5C can reach as high as 93.7 and 96.6%, respectively. Besides, improved rate capabilities and thermal stability are also obtained for Li2 SnO3 -coated and Sn-doped materials. The superior electrochemical performances and enhanced thermal stability of Li2 SnO3 coated samples are mainly ascribed to the higher interfacial stability and those of Sn-doped materials may be mainly due to higher structural stability and lower polarization than those of the bare LiNi0.8 Co0.1 Mn0.1 O2 cathode material. These results indicate that the introduction of Sn ions, especially Sn doping, may be an effective strategy to improve the performance of Ni-rich layered cathode materials.